Assessment of Usnic Acid (Lichen Usnea Articulata Extract) Safety on Lipid Profile, Adipocytes Morphology and Liver Functions in Adult Male Rats - Ahlam A. Al Ahmadi (Journal of King Abdulaziz University: Medical Sciences, 2023)
Absorption and plasma level of usnic acid and safety of lichen Usnea articulate extract, usnic acid, were assessed in adult male Sprague-Dawley rats. Three groups (N = 10) were used: Group I received [1% carboxymethylcellulose (CMC)], Group II received extract/CMC (100 mg/kg), and Group III received extract/CMC (300 mg/kg) orally for 7 weeks. Usnic acid reached peak within 6 hr, remained in circulation for 72 hr after oral administration of 500 mg UA/kg. The extract results in significant increase in food intake at 2nd, 4th, 5th weeks in Group III versus controls. At 7th week, Group II showed an increase in albumin, total bilirubin, total cholesterol and high density lipoprotein cholesterol (HDL-C). In Group III glucose, magnesium, total bilirubin, alanine aminotransferase (ALT), total cholesterol, HDL-C, low density lipoprotein cholesterol (LDL-C), liver index were increased while aspartate aminotransferase (AST), lactate dehydrogenase (LDH) were decreased. Group II showed an increase in food efficiency, (LDH) but a decrease in glucose, magnesium, total bilirubin, (ALT), total cholesterol, LDL-C, HDL-C and liver index versus Group III.Usnea articulate extract exerted dose-dependent effects on body weight, liver functions, lipid profile and glucose with potential safety in low dose; affected adipocyte morphology and morphometry in high dose.